Private Life and Collective Experience in Quebec: The Autobiographical Project of France Théoret - Mary Jean Green (Studies in 20th & 21st Century Literature, 1993)
In her study of women's autobiographical writing, Carolyn Heilbrun contends that women's authorship has been most hindered by the lack of narrative structures adequate to the telling of women's experience. She further suggests that female narrative will be found as women talk together, exchange stories, and move toward a collective understanding of self. In recent years, the interplay of women's voices has assumed new importance in women's writing, and specifically in women's life/writing in French. Perhaps beginning with Simone de Beauvoir's feminist classic, The Second Sex, where the words of hundreds of other women are woven into the text to form an understanding of the shape of a woman's life, this new form of women's narrative is apparent in the autobiographical project of the Quebec Francophone writer France Théoret. In her novel Nous parlerons comme on écrit, the interplay of different voices and the interlocking and mirroring of disparate narratives enable Théoret to construct a female autobiographical subject that encompasses the reality of several generations of Quebec women. Théoret's work is thus, like that of the Algerian Francophone writer Assia Djebar, an example of a new narrative form that has emerged from women's collective efforts to construct a new female self, a sort of feminist collective autobiography.
Keywords: women' s autobiographical writing; autobiography; women writing; Carolyn Heilbrun; women' s authorship; narrative structures; women' s experience; female narrative; self; collective understanding; women' s voices; women' s voice; life; writing; French; imone de Beauvoir; feminist classic; The Second Sex; narrative; Quebec Francophone; Quebec; France Théoret; Nous parlerons comme on écrit; disparate narratives; generation; generations; Algerian Francophone; Algerian; Assia Djebar; feminist collective autobiography; feminism; feminist